Aspek Hukum Dalam Perjanjian Kerjasama Antara PT. Telkom Dengan PT. Sandhy Putra Makmur Dalam Penggunaan Tenaga Kerja - Mulyono, Sri, Nuswardhani, S.H, S.U, Shalman Al Farizi, S.H., M.Kn (2016)
The purpose of this study was to analyze the rules, processes, and type of cooperation agreement between PT labor. Telkom and PT. Sandy Putra Makmur and legal responsibility if one of the parties made a mistake. This research includes normative legal research. Data were analyzed using qualitative analysis. The results showed that: First, Regulations and agreements that are used in the implementation of the cooperation agreement between PT labor. Telkom and PT. Sandhy Putra Makmur is an agreement of contract of work; Second, the obligation of PT. Telkom is handed a job contract at PT. Sandhy Putra Makmur, pay chartering services to the PT. Sandhy Putra Makmur as agreed in the agreement. What are the rights of PT. Telkom is the obligation of PT. Sandhy Putra Makmur; Third, the error PT. Sandhy Putra Makmur not carry out its obligations to employees as well as to the PT. Telkom resulting event of default and the other party (PT. Telkom) harmed. Parties who are in default or tort must provide compensation.